PECULIARITIES OF IDEAS ABOUT LOVE AT DIFFERENT STAGES OF ONTOGENESIS - Abduvakhabova Dinora Abdusoat Qizi (Western European Studies, 2024)
In this article, we have studied the characteristics of ideas about love at different stages of ontogenesis, as well as the value orientations of modern youth, their life goals and a certain direction of their actions. Improving their professional skills, forming a strategy for achieving goals, and observing social norms will depend on the development of value orientations of young students
Keywords: gender; student-youth; values